Improving treatment for patients with childhood abuse related posttraumatic stress disorder (IMPACT study): protocol for a multicenter randomized trial comparing prolonged exposure with intensified prolonged exposure and phase-based treatment - D. A. C. Oprel; C. M. Hoeboer; M. Schoorl; R. A. De Kleine; I. G. Wigard; M. Cloitre; A. Van Minnen; W. Van der Does (BMC Psychiatry, 2018)
Abstract Background Childhood abuse related posttraumatic stress disorder (CA-PTSD) is associated with a high burden of disease and with treatment response rates that leave room for improvement. One of the treatments for PTSD, prolonged exposure (PE), is effective but has high drop-out rates and remission rates are relatively low. An intensified form of PE (iPE) was associated with good response and low drop-out rates in PTSD and has not yet been tested in a controlled trial in CA-PTSD. Phase-based treatment (PBT), in which PE is preceded by skills training may improve overall outcomes in this population. We will assess the effectiveness and cost-effectiveness of standard PE, iPE and PBT in patients with CA-PTSD. Methods/design Multi-center randomized controlled trial. Treatment conditions are: prolonged exposure (PE; maximum of 16 sessions in 16 weeks); intensified PE (iPE; maximum of 12 sessions in four weeks and two booster sessions); phase-based treatment (PBT; maximum of eight sessions skills training followed by eight sessions PE in 16 weeks). Primary outcome: Clinician-rated PTSD symptom severity. Secondary outcomes: loss of PTSD diagnosis, self-reported PTSD symptom severity, comorbid symptom severity and quality of life. Moreover, we will examine cost-effectiveness and moderators and mediators of treatment outcome. Target population: adults with CA-PTSD (N = 150). Assessments in weeks 0, 4, 8, 16, 26 and 52. Discussion Given that no consensus yet exists about the treatment guidelines for patients with CA-PTSD, the present study may have important implications for the treatment of CA-PTSD. Trail registration Registered at C.C.M.O. on Sept 7, 2016 (NL57984.058.16); retrospectively registered at June 21, 2017 at clinicaltrials.gov identifier: NCT03194113.